The Relation between Rice Productivity in Ingin Jaya Subdistrict and NDVI (Normalized Difference Vegetation Index) from Surface Reflectance data of LANDSAT 8. Issue 1 (March 2020) - Ardiansyah,; Nizamuddin,; Amalia, S
Abstract: Rice has an important role as the staple food for most of Indonesian people. Therefore, to ensure the sufficiency of rice stocks, it is necessary to estimate crop production from existing rice fields before they are harvested. This research was conducted to find the relationship between Normalized Difference Vegetation Index (NDVI) and rice productivity of rice fields in Ingin Jaya Subdistrict, Aceh Besar District, Aceh Province. The NDVI was calculated from the surface reflectance data of Landsat 8. The results showed that the NDVI in the study area ranged from 0.4 to 0.84. These results were higher than the NDVI calculated from the Landsat 8 L1 data, which ranged from 0.26 to 0.49. The productivity of rice fields were calculated for 21 locations of sample plot. Based on the calculations, the lowest productivity was 2.047 kg/m2, and the highest was 10.462 kg/m2. The relation between NDVI and the productivity was tested using the Pearson correlation, but the results showed that there was no significant relation between the NDVI and the rice field productivity in Ingin Jaya Subdistrict.